Cultural Perspective in The Translation of Slang Expressions in Subtitle Die Hard 3 - Rahmawati Sukmaningrum; Ajeng Setyorini (ETERNAL (English Teaching Journal), 2017)
The paper focuses upon the problem of trans-cultural transfer in subtitling of Die Hard 3 movie dialogues. Language and culture may thus be seen as being closely related and both aspects must be considered for translation. The methodology of the research involves analysis of the type and function of slang expressions and their translating strategies viewed from cultural perspective. The data reveal that in translation process the translator used the effect of softening. The consideration of the target reader is taken account in choosing the translation strategies. As the result, the authors found 7 specific slang expressions that were translated using loan translation. Meanwhile, the total number of general slang expressions from the mivie was 90. There are six strategies applied by the translator to translate the slang expressions that belong to general slang type. They are; (1) Translating General Slang using common word or phrase of similar expressive meaning, (2) Translating General Slang using Shift or Translating General Slang using Transposition, (3) Translating General Slang using Ommision, (4) Translating General Slang using Cultural Equivalent, (5) Translating General Slang using Swearing Words in Target Language, and (6) Translating General Slang using Synonymy.